Pengaruh Ketepatan Waktu Pengiriman dan Harga terhadap Kepuasan Konsumen pada Ninja Xpress Sampit - Atmoko, Parni Tri (Keizai, 2022)
The aim is to analyze the effect of on-time delivery and price on customer satisfaction with Ninja Xpress Sampit. The phenomenon in this study is, based on data on the delivery of goods in 2021, there are many delays in the delivery of goods. Then the problem of price or shipping rates on Ninja Xpress Sampit is more expensive than other logistics companies. Quantitative research and sample collection technique used a non-probability sampling method through a convenience sampling approach and 100 people as samples. The data were analyzed by multiple regression, and the test was carried out using SPSS 22. The results of the partial study showed that the variable on the delivery time (X1) had a significant and positive effect on consumer satisfaction and price (X2) also had a significant and positive impact on customer satisfaction with a value of each having the same significance, namely 0.00 < 0.05. Where the level of significance is below 0.05, H1 and H2 are accepted, meaning that the delivery time and price have a significant effect on customer satisfaction with Ninja Xpress Sampit.